2018
DOI: 10.3171/2017.4.jns162143
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic endonasal approach for craniopharyngioma: the importance of the relationship between pituitary stalk and tumor

Abstract: OBJECTIVE The endoscopic endonasal approach (EEA) is commonly used for the treatment of craniopharyngioma; therefore, it is essential to analyze outcomes in order to understand the benefits and drawbacks. The goal of this paper was to evaluate the clinical features and outcomes associated with this treatment approach. METHODS From July 2010 to March 2016, 82 adult craniopharyngioma patients underwent an EEA at the authors' institution. Of these cases, intraoperative records and immediate postoperative MR image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 35 publications
3
40
1
Order By: Relevance
“…The pulled dural window served as a protective barrier for the surgical window from the blood coming from the sphenoid or from between the dural and skull base bone during the operation. The tumor was always dissected and removed with microsurgical techniques, and the details were not different from those in previous reports [ 14 , 36 , 38 , 54 ]. The loose approximation of bilateral dura after the removal of the tackup suture was the first step of the reconstruction process.…”
Section: Methodsmentioning
confidence: 99%
“…The pulled dural window served as a protective barrier for the surgical window from the blood coming from the sphenoid or from between the dural and skull base bone during the operation. The tumor was always dissected and removed with microsurgical techniques, and the details were not different from those in previous reports [ 14 , 36 , 38 , 54 ]. The loose approximation of bilateral dura after the removal of the tackup suture was the first step of the reconstruction process.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, since a significant proportion of patients are subjected to adjuvant radiotherapy a baseline assessment enables tracking neurocognitive changes that may occur after radiation. Some authors reported no changes in neuropsychological performance after surgical procedures [78] while others describe improvement of preoperative cognitive dysfunction and memory [37]. However, reported postoperative morbidity includes cognitive dysfunction with attention deficit, impaired episodic memory, and processing speed [50,140], which were associated with microstructural alterations of the white matter tracts detected with the use of DTI [51].…”
Section: Evidencementioning
confidence: 99%
“…Expanded endonasal approaches (EEA), through a transtubercular approach (with or without a transplanum route), allow an excellent exposure of the tumor without crossing crucial neurovascular structures [17,25,26,34,37,57,60,61,94,107]. Furthermore, the direct access through the endonasal route has the advantage of early identification of the superior hypophyseal arteries, which are important for the optic apparatus and also of early identification of the chiasm and optic nerves thus avoiding retraction not only of the nerves but also of the basal frontal lobes.…”
Section: Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…raniopharyngiomas (CPs) are benign rare tumors thought to arise from embryonic remnants of Rathke's pouch. 2,9,10,43,45 Gross-total resection (GTR) remains the gold standard treatment of CPs, although comparable control rates have been reported with subtotal resection (STR) and adjuvant radiation therapy (RT). 43 The development of the endoscopic endonasal approach (EEA) has helped to improve visualization of the sellar and suprasellar region, while eliminating the need for brain retraction and minimizing manipulation of surrounding critical neurovascular structures.…”
mentioning
confidence: 99%